2016
DOI: 10.1038/srep36631
|View full text |Cite
|
Sign up to set email alerts
|

A scFv antibody targeting common oligomeric epitope has potential for treating several amyloidoses

Abstract: Overproduction or poor clearance of amyloids lead to amyloid aggregation and even amyloidosis development. Different amyloids may interact synergistically to promote their aggregation and accelerate pathology in amyloidoses. Amyloid oligomers assembled from different amyloids share common structures and epitopes, and are considered the most toxic species in the pathologic processes of amyloidoses, which suggests that an agent targeting the common epitope of toxic oligomers could provide benefit to several amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Therefore, oligomer‐specific epitopes have become promising targets of immunotherapeutic interventions in AD (Guerrero‐Munoz, Castillo‐Carranza, & Kayed, 2014). Indeed, our previous reports and the results of the present study demonstrated that oligomer‐specific vaccines and antibodies significantly reduced brain pathology and prevented cognitive deficits in models of AD in mice (Wang et al, 2017; Zha et al, 2016; Zhao et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, oligomer‐specific epitopes have become promising targets of immunotherapeutic interventions in AD (Guerrero‐Munoz, Castillo‐Carranza, & Kayed, 2014). Indeed, our previous reports and the results of the present study demonstrated that oligomer‐specific vaccines and antibodies significantly reduced brain pathology and prevented cognitive deficits in models of AD in mice (Wang et al, 2017; Zha et al, 2016; Zhao et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…The Morris water maze (MWM) consisted of a pool (110 cm in diameter) containing opaque water (22 ± 1°C) and a platform (10 cm in diameter) submerged 1 cm under the water (Zha et al, 2016). Hidden platform training was conducted twice per day for five consecutive days with an inter‐trial interval of 3–4 hr.…”
Section: Methodsmentioning
confidence: 99%
“…, ) Recently, scFv W20 that recognizes various oligomers targeting the common epitopes of amyloid oligomers was found to reduce α‐syn and mutant huntingtin protein aggregate load in mouse models, leading to reduced synaptic degeneration, neuroinflammation, and oxidative stress, concomitant with amelioration of cognitive and motor deficits (Zha et al . ). Spencer et al .…”
Section: Antibody Fragments Targeting α‐Synmentioning
confidence: 97%
“…These scFv recognized amyloid oligomers in all types of plaques, Lewy bodies, and amylin deposits in the brain tissues of AD and PD patients and in the pancreas of type 2 diabetes patients ). Other scFv antibodies, including 10H and D5, were found to recognize morphologically distinct a-syn oligomers and selectively bind to aggregates in post-mortem human PD brain tissues and inhibit toxicity in a cell model (Emadi et al 2007(Emadi et al , 2009 Recently, scFv W20 that recognizes various oligomers targeting the common epitopes of amyloid oligomers was found to reduce a-syn and mutant huntingtin protein aggregate load in mouse models, leading to reduced synaptic degeneration, neuroinflammation, and oxidative stress, concomitant with amelioration of cognitive and motor deficits (Zha et al 2016). Spencer et al (2014) fused the scFv fragment, targeting oligomeric a-syn, to low-density lipoprotein receptor-binding domain from apolipoprotein B, improving its therapeutic potential by increasing accumulation of scFv in the brain and directing scFv/a-syn complexes for degradation through the endosomal sorting pathway (Spencer et al 2014).…”
Section: Antibody Fragments Targeting A-synmentioning
confidence: 99%
“…ROS assay was performed as previously described [31]. Brie y, ROS production was uorometrically monitored using 2, 7-dichloro uorescein diacetate (DCFDA) mixed with the brain lysates.…”
Section: Measurement Of Gsh Gssg and Rosmentioning
confidence: 99%